Émile Benoit at the club in Mainland during the talent show - Foley, Margaret (1990)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « My Field Trip to Mainland and Black Duck Brook on the Port au Port Peninsula, Newfoundland ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "My Field Trip to Mainland and Black Duck Brook on the Port au Port Peninsula, Newfoundland".